Chain Drill Technique in Teaching Speaking - Ika Paramitha Lantu (Sintuwu Maroso Journal of English Teaching, 2017)
This research aims to find out the influence of Chain Drill Technique in teaching speaking to the tenth grade students at SMAN 1 Poso, particularly in describing an object. This research is quantitative in nature and the design was pre-experimental. The researcher applied pre-test and post-test in collecting the data. The result of data analysis shows chain drill technique in teaching speaking can increase students speaking achievement in describing an object.Keywords: chain drill, technique, speaking achievement